The Incidence of Fall and Past History of Falling in Aged Hospitalized Patients - Dadgari 1, Ali; Mirrezaee 2*, Seyed Mohammad; Hojati 3, Hadi (Shahroud Journal of Medical Sciences, 2019)
Background: Identifying elderly people with the risk of fall in hospitalsis particularly important for prevention of falls. Review of literaturesuggested that the association between falls and some characteristicsof geriatric inpatients. The aim of this study was to determine thepredisposing factors of falling among the elderly hospitalized patients.Methods: In this descriptive-analytic cross-sectional study, 1213elderly hospitalized patients, 60 years old and above recruited toparticipate in the study. Of all participant 385 subjects met theinclusion criteria of the study. Data collected from a secondary studyon falls which was conducted from March to December 2016. Ademographic questionnaire and Johns Hopkins fall risk assessmenttool were used to evaluate the falls incident and risk of fall among theelderly people. The scores were analyzed by SPSS software version 16.Chi square test and exact test of Fisher and logistic regression wereemployed for data analysis. Significance level was set at 0.05.Results: The mean of age in the subjects was 71.68 + 8.32 years old.Off all 385 eligible aged hospitalized patients, the rate of fallsestimated to be 1.05 per 1000 bed-day. Approximately 12% of casesexperienced at least one fall during hospitalization period. Accordingto the results of logistic regression analysis, the most predisposingfactors for falls in hospital was the past history of falling with oddsratio of 12.7. Moreover, older age (age ≥ 80 years old), use ofmedication/equipment, low cognitive ability, and polypharmacy withodds ratios of 2.63, 1.49, 2.26, 0.988, and 3.34 were related to thefalling in the past, respectively.Conclusions: The results of the study indicated that the incident of fallsamong geriatric patients were relatively low, due to clinicalinterventions in hospital to prevent falls or to routine underestimationand under report of falls.